Impact of Fe(III) (Oxyhydr)oxides Mineralogy on Iron Solubilization and Associated Microbial Communities - Zhang, Fengfeng; Battaglia-Brunet, Fabienne; Hellal, Jennifer; Joulian, Catherine; Gautret, Pascale; Motelica-Heino, Mikael (Frontiers in Microbiology, 2020)
Iron-reducing bacteria (IRB) are strongly involved in Fe cycling in surface environments. Transformation of Fe and associated trace elements is strongly linked to the reactivity of various iron minerals. Mechanisms of Fe (oxyhydr)oxides bio-reduction have been mostly elucidated with pure bacterial strains belonging to Geobacter or Shewanella genera, whereas studies involving mixed IRB populations remain scarce. The present study aimed to evaluate the iron reducing rates of IRB, enriched consortia originating from complex environmental samples, when grown in presence of Fe (oxyhydr)oxides of different mineralogy. The abundances of Geobacter and Shewanella were assessed in order to acquire knowledge about the abundance of these two genera in relation to their effects on kinetic control of mineralogical Fe (oxyhydr)oxides reductive dissolution. Laboratory experiments were carried out with two freshly synthetized Fe (oxyhydr)oxides presenting contrasting specific surfaces, and two defined Fe-oxides, i.e., goethite and hematite. Three IRB consortia were enriched from environmental samples from a riverbank subjected to cyclic redox oscillations related to flooding periods (Decize, France): an unsaturated surface soil, a flooded surface soil and an aquatic sediment, with a mixture of organic compounds provided as electron donors. The consortia could all reduce iron-nitrilotriacetate acid (Fe(III)-NTA) in 1-2 days. When grown on Fe (oxyhydr)oxides, Fe solubilisation rates decreased as follows: fresh Fe (oxyhydr)oxides > goethite > hematite. Based on a bacterial rrs gene fingerprinting approach (CE-SSCP), bacterial community structure in presence of Fe(III)-minerals was similar to those of the site sample communities from which they originated but differed from that of the Fe(III)-NTA enrichments. Shewanella was more abundant than Geobacter in all cultures. It’s abundance was higher in presence of the most efficiently reduced Fe (oxyhydr)oxide than with other Fe(III)-minerals. Geobacter however, was more abundant in presence of less easily solubilised Fe (oxyhydr)oxides. This study highlights the influence of Fe mineralogy on the abundance of Geobacter and Shewanella in relation to Fe bio-reduction kinetics in presence of a complex mixture of electron donors.